Pediatric Hand Injuries Requiring Closed Reduction at a Tertiary Pediatric Care Center. (March 2021) - Market, Marisa; Bhatt, Maala; Agarwal, Amisha; Cheung, Kevin
Background: Hand fractures and dislocations are common injuries in the pediatric population. This study aims to characterize the pediatric hand injuries that required closed reduction and identify those that required multiple reduction attempts.Methods : A retrospective cohort study was carried out in patients younger than 18 years of age with hand fractures or dislocations who underwent closed reduction in the emergency department (ED). Patients who ultimately required surgical reduction and fixation were not included.Results : Of the 310 hand injuries identified, 148 (114 fractures and 34 dislocations) underwent closed reduction in the ED; 7.4% of those required repeat reduction. Hand injuries that most often required repeat reduction included metacarpophalangeal joint dislocations (20.0%) and proximal phalanx neck (16.7%), metacarpal shaft (15.4%), metacarpal neck (6.2%), and proximal phalanx base (5.6%) fractures. No modifiable risk factors predicting the need for repeat reduction were identified.Conclusions : Some pediatric hand injuries are more likely to require repeat closed reduction by a hand surgeon. This retrospective study is the first step toward quality improvement as it provides opportunities for further research into the factors contributing to reductions that are unsuccessful at the first attempt. Identification of these factors and implementation of quality improvement measures are necessary to ensure the effective treatment of all pediatric hand injuries.